2021
DOI: 10.25081/ia.2021.v4.6899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different age of seedlings on the growth and yield performance of transplanted Aus rice variety

Abstract: An experiment was conducted in the Agriculture Field Laboratory, Noakhali Science and Technology University (NSTU) to evaluate the effects of age of seedlings on the yield and growth performance of transplanted Aus (T. Aus) rice variety from April 2019 to July 2019. The experiment was carried out assigning four age of seedlings (T1 = 22-day old, T2 = 24-day old, T3 = 27-day old, T4 = 30-day old) and two rice varieties (V1 = BRRI dhan83, V2 = BRRI dhan65). The experiment was laid out in a Randomized Complete Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
2
2
0
Order By: Relevance
“…The result obtained from the present study was similar to the findings of Islam et al (2021a) and reported that, the highest harvest index was obtained from younger seedlings. Also, the highest harvest index (43.03%) was found in 75% of RDF + poultry manure @ 2.5 t ha -1 and the lowest harvest index (41.60%) was obtained from treatment 50% of RDF + Cow-dung @ 5 t ha -1 (Table 3).…”
Section: Harvest Indexsupporting
confidence: 92%
See 1 more Smart Citation
“…The result obtained from the present study was similar to the findings of Islam et al (2021a) and reported that, the highest harvest index was obtained from younger seedlings. Also, the highest harvest index (43.03%) was found in 75% of RDF + poultry manure @ 2.5 t ha -1 and the lowest harvest index (41.60%) was obtained from treatment 50% of RDF + Cow-dung @ 5 t ha -1 (Table 3).…”
Section: Harvest Indexsupporting
confidence: 92%
“…The highest biological yield (7.30 t ha -1 ) was recorded at 30 days old seedling which is significantly higher than 45 days old seedlings (6.85 t ha -1 ) and 60 days old seedlings (6.34 t ha -1 ) (Table 3). The result obtained from the present study was similar with the findings of Islam et al (2021a) and reported that, the highest biological yield (9.23 t ha -1 ) was obtained from 30 days old seedlings. Chakrabortty (2013) reported that, seedling age varied the biological yield of rice under SRI.…”
Section: Biological Yieldsupporting
confidence: 92%
“…Low seedling age (20-day) produced the tallest plant (36.26 cm) at 15 DAT while moderate seedling age (30-day) produced the tallest plant (67.35 cm) at 45 DAT. Islam et al (2021) documented that proper age of seedlings had helped rice plants to complete its vegetative phase in favorable climatic conditions resulting in tallest plant. Again, 4 seedlings hill -1 produced the tallest plant (36.58, 52.72, 69.81 and 74.49 cm, respectively) at 15, 30, 45 and 60 DAT, respectively.…”
Section: Plant Heightmentioning
confidence: 99%
“…BRRI has developed some short duration rice cultivars like BRRI dhan56, BRRI dhan66 and BRRI dhan71 . Seedling age is also an important factor due to its tremendous influence on the plant height, tiller production, panicle length, grains per panicle and other yield contributing characters (Luna et al, 2017;Sinha et al, 2018;Virk et al, 2020;Islam et al, 2021). The practice of transplanting seedling at different days having different ages is termed as staggered planting.…”
Section: Introductionmentioning
confidence: 99%